Self-monitoring of blood glucose and glycaemic control in type 2 diabetes - Tengblad, Anders (Informa Healthcare, 2007)
OBJECTIVE: Previous studies have shown inconsistent results with regard to whether or not self-monitoring of blood glucose (SMBG) is related to better glycaemic control in type 2 diabetes. The aim of this study was to explore the use of SMBG and its association with glycaemic control in patients with type 2 diabetes in primary care. DESIGN: A cross-sectional observational study was conducted in 2003 at 18 primary health care centres in Sweden, in which all known patients with diabetes were surveyed. The study included 6495 patients with type 2 diabetes. A sample of 896 patients was selected for further exploration of data from medical records. A telephone interview was performed with all patients in this group using SMBG (533 patients). RESULTS: There were no differences in HbA1c levels between users (6.9%) and non-users (6.8%) of SMBG in patients treated with insulin or in patients treated with oral agents (6.3% in both groups). In patients treated with diet only, users of SMBG had higher levels of HbA1c compared with non-users (5.5% vs. 5.4%, p =0.002). Comparing medical records between users and non-users of SMBG showed no differences in diabetes-related complications in any treatment category group. CONCLUSION: The use of SMBG was not associated with improved glycaemic control in any therapy category of patients with type 2 diabetes in primary care. The absence of difference in glycaemic control between users and non-users of SMBG could not be explained by differences in comorbidity between users and non-users of SMBG.